PERPADUAN BATIK MOTIF SEKAR JAGAD KHAS KUDUS, BLUDRU DAN BROKAT PADA BUSANA PESTA GALA - Sri Purwani; Aisa Ratna Sedonya (Jurnal Socia Akademika, 2022)
This study aims to: (1) Knowing the concept of combining The Batik Fabric of Sekar Jagad Khas Kudus, Bludru and Brocade with ornate ornaments on Gala Party Clothes to make it look unique and exclusive; (2) Knowing the results of the combination of Batik Sekar Jagad Khas Kudus, Bludru and Brocade Fabrics in Gala Party Clothes. Research with a qualitative approach model with descriptive methods. The subject of the study was the Combination of Batik Sekar Jagad Khas Kudus, Bludru and Brocade Fabrics, while the object of this study was gala party fashion. Data sources are obtained from experiments and data collection through Questionnaires. Collect data using: (1) Questionnaire (Questionnaire); (2) Documentation Data. Data analysis uses descriptive analysis; the researcher seeks to analyze the data obtained related to the subject matter and then describe and make conclusions. Based on the results of the study: (1) Producing a form in the form of a concept, the gala party fashion design drawing consists of a long dress and a long robe, a combination of materials, namely Sekar Jagad Khas Kudus Batik Cloth, Bludru and Brocade, complete with details and accents; (2) Producing a form or fashion work of gala party consisting of a combination of batik fabrics Sekar Jagat khas kudus, bludru, brocade. In gala fashion, sequin ornaments and beads are applied, trimming with Tula Shimmer and Tula Kaku Fabrics, Making shoulder shields from Batik Sekar Jagad Khas Kudus Fabric and Applying long and short stem sequins, crystals, sand, disks and parels on clothes according to the design.